Improving the Learning Outcomes of Science Material on Changes in Living things Through Cooperative Learning Method of STAD model in grade III students - Martini, Martini (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The average daily test score obtained by 20 third grade students at SD N 1 Jiwan on the material of changes in living things is only 60 and only 50% have reached the minimum learning completeness criteria of 70 (KKM). Based on the reflection carried out by the researcher, the problem was identified that (1) third grade students of SD N 1 Jiwan could not understand the material of changes in living things so that it had an impact on the lack of learning outcomes obtained by students. (2) Teachers do not use varied methods in learning, teachers only use the lecture method when doing learning. This research uses PTK. The results of this study The STAD model cooperative learning method has a positive impact in improving student learning achievement which is marked by an increase in student learning completeness in each cycle, namely cycle I (57.14%), cycle II (71.42%), cycle III (85.71%).